IMPLEMENTASI PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI AUGMENTED REALITY PADA PEMBELAJARAN MATEMATIKA DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV MI SUNAN BONANG II - Fauziah, Jeni; Zainuddin, Zainuddin; Amalia, Nur Fitri (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
Along with the development of the times, technology in education is also increasingly developing, especially in improving students' critical thinking skills. Mathematics is one of the compulsory subjects studied in elementary school which is able to improve students' critical thinking skills. In the process, teachers play a very important role in creating a learning atmosphere that can stimulate students' critical thinking skills. This study aims to describe how the use of Augmented Reality technology in mathematics lessons improves the critical thinking skills of grade IV students of MI Sunan Bonang II. This type of research is qualitative research, namely the researcher describes how the use of Augmented Reality technology in mathematics lessons to improve students' critical thinking skills. The subjects in this study were the principal, subject teachers and all grade IV students of MI Sunan Bonang II in the 2024/2025 academic year with a total of 15 students consisting of 8 female students and 7 male students. Data collection techniques in this study used observation, interview and documentation techniques. The results of the study showed that there was a significant change, namely that students' critical thinking skills increased after the use of Augmented Reality technology in mathematics lessons.